Theoretical Performance of BaSnO3-Based Perovskite Solar Cell Designs Under Variable Light Intensities, Temperatures, and Donor and Defect Densities - Nouf Alkathran; Shubhranshu Bhandari; Tapas K. Mallick (Designs)
Barium stannate (BaSnO3) has emerged as a promising alternative electron transport material owing to its superior electron mobility, resistance to UV degradation, and energy bandgap tunability, yet BaSnO3-based perovskite solar cells have not reached the efficiency levels of TiO2-based designs. This theoretical study presents a design-driven evaluation of BaSnO3-based perovskite solar cell architectures, incorporating MAPbI3 or FAMAPbI3 perovskite materials, Spiro-OMeTAD, or Cu2O hole transport materials as well as hole-free configurations, under varying light intensity. Using a systematic device modelling approach, we explore the influence of key design variables—such as layer thickness, donor density, and interface defect concentration—of BaSnO3 and operating temperature on the power conversion efficiency (PCE). Among the proposed designs, the FTO/BaSnO3/FAMAPbI3/Cu2O/Au heterostructure exhibits an exceptionally effective arrangement with PCE of 38.2% under concentrated light (10,000 W/m2, or 10 Sun). The structure also demonstrates strong thermal robustness up to 400 K, with a low temperature coefficient of −0.078% K−1. These results underscore the importance of material and structural optimisation in PSC design and highlight the role of high-mobility, thermally stable inorganic transport layers—BaSnO3 as the electron transport material (ETM) and Cu2O as the hole transport material (HTM)—in enabling efficient and stable photovoltaic performance under high irradiance. The study contributes valuable insights into the rational design of high-performance PSCs for emerging solar technologies.